2017
DOI: 10.5350/dajpn2017300202
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of childhood trauma, dissociative experiences and depression with pain in female patients with fibromyalgia: a cross-sectional study

Abstract: The relationship of childhood trauma, dissociative experiences and depression with pain in female patients with fibromyalgia: a cross-sectional studyObjective: The aim of this study was to investigate childhood trauma (CT) and dissociative symptoms in patients with fibromyalgia and evaluate the relationship of these characteristics with pain intensity. Methods: Forty patients followed up with fibromyalgia diagnosis in the physical therapy and rehabilitation outpatient clinic; and as a control group, 38 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…With the exception of emotional neglect, the experiment group scored higher than the control group in the other four sub-dimensions of the CTQ. These results were consistent with the findings of previous studies with [11,12,26,27] and without a control group [9,14,17] which emphasized the presence of exposure to childhood trauma in FM patients. The incidence of emotional abuse was dramatically higher in the FM patients than in the control group, which was consistent with studies that have reported the essential forms of trauma related to fibromyalgia to be emotional [11,12,26,29].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With the exception of emotional neglect, the experiment group scored higher than the control group in the other four sub-dimensions of the CTQ. These results were consistent with the findings of previous studies with [11,12,26,27] and without a control group [9,14,17] which emphasized the presence of exposure to childhood trauma in FM patients. The incidence of emotional abuse was dramatically higher in the FM patients than in the control group, which was consistent with studies that have reported the essential forms of trauma related to fibromyalgia to be emotional [11,12,26,29].…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with the findings of previous studies with [11,12,26,27] and without a control group [9,14,17] which emphasized the presence of exposure to childhood trauma in FM patients. The incidence of emotional abuse was dramatically higher in the FM patients than in the control group, which was consistent with studies that have reported the essential forms of trauma related to fibromyalgia to be emotional [11,12,26,29]. The findings were also consistent with the literature in respect of more physical trauma reported by FM patients than the control group [12,26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While these trigger points may arise as a result of central nervous system sensitisation, alternatively, the trigger points could contribute to the development of fibromyalgia syndrome, as the presence of peripheral trigger points has been shown to contribute to central sensitisation (Shah & Heimur, 2012). Karas et al (2017) found that people with fibromyalgia had a higher rate of childhood trauma, were more likely to dissociate and/or report somatoform disorders. These authors suggested that fibromyalgia clients may benefit from emotional processing techniques.…”
Section: Literature Reviewmentioning
confidence: 97%
“…While fibromyalgia is generally considered a condition of the nervous system, there is evidence that other systems are affected. Systemic inflammation and neuro-inflammation (Bäckryd, 2017;Littlejohn, 2015), myofascial trigger points (Shah & Heimur, 2012;Cakit et al, 2010), dissociation and somatoform disorders (Karas et al, 2017) are all associated with fibromyalgia. Shah and Heimur (2012) note that people with fibromyalgia are much more likely to have trigger points than the general population.…”
Section: Literature Reviewmentioning
confidence: 99%